Kalimat Perintah dalam Terjemahan Al-Qur’an Surah An-Nahl - Rahmi, Rahmi; Saleh, Muhammad; Sultan, Sultan (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2023)
This study aims to: describe the form of command sentences in the translation of the Al-Qur'an surah An-Nahl; Describing imperative sentence markers in the translation of Al-Qur'an Surah An-Nahl; Describe the contents of the command sentence in the translation of the Al-Qur'an surah An-Nahl. This type of research is qualitative with a descriptive design. The research data are in the form of words, phrases, and sentences that contain imperative sentences in the translation of the Al-Qur'an surah An-Nahl. The source of this research data comes from the translation of the Al-Qur'an surah An-Nahl. The data collection technique was carried out through reading and noting techniques. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study reveal that there are five forms of imperative sentences in the translation of Al-Qur'an surah An-Nahl, namely: (1) ordinary imperative sentences; (2) request command sentences; (3) imperative sentences of invitation; (4) sentences of orders; and (5) prohibition orders. The markers in the translation of the Al-Qur'an surah An-Nahl include six markers, namely: (1) the use of the particle -lah; (2) the use of the -kan suffix; (3) the use of exclamation marks (!); (4) the use of question marks (?); (5) the use of the word order; and (6) the use of the word whoever. Then there are five contents of command sentences in the translation of Al-Qur'an surah An-Nahl, namely: (1) aqidah and monotheism; (2) worship; (3) law; (4) morals; and (5) science